2018
DOI: 10.1111/anu.12840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietaryLactobacillus delbrueckiion growth performance, body composition, digestive and absorptive capacity, and gene expression of common carp (Cyprinus carpioHuanghe var)

Abstract: The present study aimed to investigate the effects of dietary supplementation of Lactobacillus delbrueckii (L. delbrueckii) on growth performance, body composition, intestinal enzyme activities and gene expression of Cyprinus carpio Huanghe var. Fish (mean 1.05 ± 0.03 g in triplicate) were conducted for 8 weeks with five treatments in triplicate. The fish in the control were fed a basal diet, and those in D2, D3, D4 and D5 were fed basal diet containing L. delbrueckii at 1 × 10 CFU/g, 1 × 10 CFU/g, 1 × 10 CFU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…In the present study, proximate analysis of muscle tissue showed significant increase in crude protein and lipid content; on the other hand, carbohydrate content was decreased when fish fed with 2 × 10 8 CFU/g of L. fermentum URLP18. Similar observations were noticed in C. carpio ‐supplemented L. delbrueckii (Zhang et al., 2018) and C. mrigala ‐supplemented commercial probiotic (Ullah et al., 2018). Further, Dash et al.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, proximate analysis of muscle tissue showed significant increase in crude protein and lipid content; on the other hand, carbohydrate content was decreased when fish fed with 2 × 10 8 CFU/g of L. fermentum URLP18. Similar observations were noticed in C. carpio ‐supplemented L. delbrueckii (Zhang et al., 2018) and C. mrigala ‐supplemented commercial probiotic (Ullah et al., 2018). Further, Dash et al.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Zhang et al. (2018) stated that Lactobacillus delbrueckii enriched diet exhibited significant growth performance in C. carpio . In addition, L. fermentum encapsulated with lactulose improved the growth performance in rainbow trout ( Oncorhynchus mykiss ) (Madreseh et al., 2019).…”
Section: Discussionmentioning
confidence: 91%
“…These 11 genera are important for degradation or crystallization and conversion of nitrogenous substances. Lactobacillus is a probiotic in animals, and it is important for healthy growth and development of the body [ 34 ]. Bacteria assigned as “uncultured bacterium” of the Bacteroidales family S24-7 were the predominant taxon in the fecal microflora at the genus level.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies did not detect bands related to these species in intestinal microbiota of specimens fed 25% U. rigida during 60 days, although these species were detected in fish receiving lower dietary Ulva supplementation (5% and 15%) (Rico et al, 2016). Lactobacillus delbrueckii subspecies have inhibited the growth of various bacteria (Akpinar et al, 2011), as well as promoting growth performance by improving digestive enzyme activities, gut microbiota and expression growth-related genes (Mohammadian et al, 2019;Zhang et al, 2019). Mohammadian et al (2019) suggested that higher colonization of L. delbruecki might be consequence of higher adhesion ability of probionts to intestinal mucosa (Liu et al, 2013) or lower intestinal pH induced by LAB species (Vendrell et al, 2008), which inhibits pathogenic microorganisms proliferation (Ringø et al, 2010).…”
Section: Evaluation Of Intestinal Microbiotamentioning
confidence: 98%